2021
DOI: 10.1186/s42397-021-00093-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of cotton germplasm for morphological and biochemical host plant resistance traits against sucking insect pests complex

Abstract: Background Sucking insect pests cause severe damage to cotton crop production. The development of insect resistant cotton cultivars is one of the most effective measures in curtailing the yield losses. Considering the role of morphological and biochemical host plant resistance (HPR) traits in plant defense, 12 cotton genotypes/varieties were evaluated for leaf area, leaf glanding, total soluble sugars, total soluble proteins, total phenolics, tannin and total flavonoids against fluctuating popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 16 publications
3
8
0
Order By: Relevance
“…These are in contrast to the findings of Deb et al (2015), Gonde et al (2015), Amin et al (2016) who reported that the higher trichome density hinders the insect movement and activity on plant. Present results corroborate those of Khan et al (2014) and partially of Murugesan and Kavitha (2010) and Rizwan et al (2021). Harishkumar (2015) reported the significant positive relation of mirid bug incidence with trichome density on lamina, midvein and leaf thickness.…”
Section: Resultssupporting
confidence: 92%
“…These are in contrast to the findings of Deb et al (2015), Gonde et al (2015), Amin et al (2016) who reported that the higher trichome density hinders the insect movement and activity on plant. Present results corroborate those of Khan et al (2014) and partially of Murugesan and Kavitha (2010) and Rizwan et al (2021). Harishkumar (2015) reported the significant positive relation of mirid bug incidence with trichome density on lamina, midvein and leaf thickness.…”
Section: Resultssupporting
confidence: 92%
“…The development of insect resistant cotton cultivars is one of the most effective measures in curtailing the yield losses. Considering the role of morphological and biochemical host plant resistance (HPR) traits in plant defense, 12 cotton genotypes/varieties were evaluated for leaf area, leaf glanding, total soluble sugars, total soluble proteins, total phenolics, tannin and total flavonoids against fluctuating populations of whitefly, thrips and jassid under field conditions (Rizwan Muhammad et al 2021).…”
Section: Ramstein Et Al (2019) Divided the Plant Breeding Process Int...mentioning
confidence: 99%
“…In one study, nymphal density and the leaf damage index of grape leafhopper (Erythroneura apicalis Nawa) were negatively correlated with CP levels in grape leaf (Fan et al, 2008). Another study reported that total soluble protein content in cotton leaves was positively associated with the population densities of thrip (Thrips tabaci), whitefly (Bemesia tabaci), and jassid (Amrasca devastans), and these pests were more prone to attack cotton genotypes with high concentrations of such proteins (Rizwan et al, 2021). Hence, the protein content of host plant leaves may be related to the degree of insect infestation, which could explain the effect of the foxtail millet materials we bred in previous work.…”
Section: Introductionmentioning
confidence: 99%